2022
DOI: 10.1007/s00497-022-00445-4
|View full text |Cite
|
Sign up to set email alerts
|

Crossover patterning in plants

Abstract: Key message Chromatin state, and dynamic loading of pro-crossover protein HEI10 at recombination intermediates shape meiotic chromosome patterning in plants. Abstract Meiosis is the basis of sexual reproduction, and its basic progression is conserved across eukaryote kingdoms. A key feature of meiosis is the formation of crossovers which result in the reciprocal exchange of segments of maternal and paternal chromosomes. This exchange generates chromosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 159 publications
0
23
0
Order By: Relevance
“…Similarly, in C. elegans , it has previously been suggested that the SC functions to prevent exchange of recombination proteins between RIs via the nucleoplasm ( Rog et al, 2017 ; Zhang et al, 2021 ; Zhang et al, 2018 ). Other studies have also recently proposed that nucleoplasm-mediated coarsening can explain CO patterning in Arabidopsis mutants with abolished synapsis, although the dynamics of this process have not been explicitly modelled ( Durand et al, 2022 ; Lloyd, 2023 ). Using our model, we provide a mechanistic explanation for why zyp1 mutants without synapsis lose both CO interference and assurance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in C. elegans , it has previously been suggested that the SC functions to prevent exchange of recombination proteins between RIs via the nucleoplasm ( Rog et al, 2017 ; Zhang et al, 2021 ; Zhang et al, 2018 ). Other studies have also recently proposed that nucleoplasm-mediated coarsening can explain CO patterning in Arabidopsis mutants with abolished synapsis, although the dynamics of this process have not been explicitly modelled ( Durand et al, 2022 ; Lloyd, 2023 ). Using our model, we provide a mechanistic explanation for why zyp1 mutants without synapsis lose both CO interference and assurance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in C. elegans , it has previously been suggested that the SC functions to prevent exchange of recombination proteins between RIs via the nucleoplasm (Rog et al, 2017; Zhang et al, 2021, 2018). Other studies have also recently proposed that nucleoplasm-mediated coarsening can explain CO patterning in Arabidopsis mutants with abolished synapsis, although the dynamics of this process have not been explicitly modelled (Durand et al, 2022; Lloyd, 2022). Using our model, we provide a mechanistic explanation for why zyp1 mutants without synapsis lose both CO interference and assurance.…”
Section: Introductionmentioning
confidence: 99%
“…Different taxa have diverse genomic properties. Some may have inherently high recombination rate or epigenetic patterns that allow them to harbour chromosomal rearrangements more easily (Henderson 2012; Lloyd 2022). Each species also has its own demographic and selection history.…”
Section: Discussionmentioning
confidence: 99%